Risk factors associated with the longevity of multi-rooted teeth. Long-term outcomes after active and supportive periodontal therapy - Salvi, Giovanni E.; Mischler, Daniel C.; Schmidlin, Kurt; Matuliene, Giedre; Pjetursson, Bjarni E.; Brägger, Urs; Lang, Niklaus P. (Journal of clinical periodontology, 2014)
Aim To investigate risk factors for the loss of multi‐rooted teeth (MRT) in subjects treated for periodontitis and enrolled in supportive periodontal therapy (SPT). Material and Methods A total of 172 subjects were examined before (T0) and after active periodontal therapy (APT)(T1) and following a mean of 11.5 ± 5.2 (SD) years of SPT (T2). The association of risk factors with loss of MRT was analysed with multilevel logistic regression. The tooth was the unit of analysis. Results Furcation involvement (FI) = 1 before APT was not a risk factor for tooth loss compared with FI = 0 (p = 0.37). Between T0 and T2, MRT with FI = 2 (OR: 2.92, 95% CI: 1.68, 5.06, p = 0.0001) and FI = 3 (OR: 6.85, 95% CI: 3.40, 13.83, p < 0.0001) were at a significantly higher risk to be lost compared with those with FI = 0. During SPT, smokers lost significantly more MRT compared with non‐smokers (OR: 2.37, 95% CI: 1.05, 5.35, p = 0.04). Non‐smoking and compliant subjects with FI = 0/1 at T1 lost significantly less MRT during SPT compared with non‐compliant smokers with FI = 2 (OR: 10.11, 95% CI: 2.91, 35.11, p < 0.0001) and FI = 3 (OR: 17.18, 95% CI: 4.98, 59.28, p < 0.0001) respectively. Conclusions FI = 1 was not a risk factor for tooth loss compared with FI = 0. FI = 2/3, smoking and lack of compliance with regular SPT represented risk factors for the loss of MRT in subjects treated for periodontitis.